N,N-Dimethylacetamide Significantly Attenuates LPS- and TNFα-Induced Proinflammatory Responses Via Inhibition of the Nuclear Factor Kappa B Pathway - Ryan Pekson; Vladimir Poltoratsky; Samir Gorasiya; Sruthi Sundaram; Charles R. Ashby; Ivana Vancurova; Sandra E. Reznik (BMC, 2016)
Abstract Previously, we have shown that N,N-dimethylacetamide (DMA) prevents inflammation-induced preterm birth in a murine model, inhibits lipopolysaccharide (LPS)-induced increases in placental proinflammatory cytokines and upregulates the antiinflammatory cytokine interleukin-10 (IL-10). However, DMA's mechanism of action remains to be elucidated. In the current study, we investigate how DMA produces its antiinflammatory effect. Using in vitro and ex vivo models, we show that DMA suppresses secretion of proinflammatory cytokines in lipopolysaccharide (LPS)-induced RAW 264.7 cells, TNFα-challenged JEG-3 cells and LPS-stimulated human placental explants. DMA significantly attenuated secretion of TNFα, IL-6, IL-10 and granulocyte macrophage colony stimulating factor (GM-CSF) from LPS-stimulated RAW 264.7 cells; IL-6 secretion from TNFα-stimulated JEG-3 cells; and TNFα, IL-6, IL-10, GM-CSF and Interleukin-8 (IL-8) from LPS-stimulated human placental explants. We further investigated whether DMA's effect on cytokine expression involves the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and mitogen-activated protein kinase (MAPK) pathways. DMA (10 mM) significantly inhibited degradation of nuclear factor of kappa light polypeptide gene enhancer in B cell inhibitor a (IκBα) in LPS-stimulated RAW 264.7 cells, but there was no significant change in the expression of phosphorylated or native forms of downstream proteins in the MAPK pathway. In addition, DMA significantly attenuated luciferase activity in cells co-transfected with NF-κB-Luc reporter plasmid, but not with AP-1-Luc or CEBP-Luc reporters. Overall, our findings suggest that the antiinflammatory activity of DMA is mediated by inhibition of the NF-κB pathway via decreased IκBa degradation.